Grammatical Cohesion Used in the Narrative Texts Written by Senior High School Students - Syifa Fauziah Irsyad; Hermawati Syarif; Refnaldi Refnaldi (Journal of English Language Teaching, 2019)
The purpose of this research is to describe the type of grammatical cohesion and the appropriate and inappropriate use of grammatical cohesion in the narrative texts written by the tenth grade students of SMAN 2 Sumatera Barat. This research was a descriptive research with quantitative approach. There were 125 students chosen as the population of this research and the sample were 30 students who selected by using random sampling method. The instrument used in this research was a writing test. To analyze the data the researcher did some steps such tabulating the data, counting the number, interpreting the result, and drawing conclusion. Furthermore, the result of this research shows that the students are able to use four types of grammatical cohesion in their writing. Those four types found are reference, conjunction, ellipsis, and substitution. Reference and conjunction were found most frequent in students’ texts with the percentage of occurring those types were 78% and 20%. In addition, ellipsis and substitution, each of them gives contribution to students’ texts just 1.5 % and 0.6%. Students tend to use the inappropriate personal reference when they try to refer between the subject and object in their sentences. From 1002 times of using grammatical cohesion, the most inappropriate use was located in using reference. The frequency of using the inappropriate reference was 72 times.